2018
DOI: 10.1038/emm.2017.239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microRNA-135a on the epithelial–mesenchymal transition, migration and invasion of bladder cancer cells by targeting GSK3β through the Wnt/β-catenin signaling pathway

Abstract: This study investigated the effects of microRNA-135a (miR-135a) targeting of glycogen synthase kinase 3β (GSK3β) on the epithelial–mesenchymal transition (EMT), migration and invasion of bladder cancer (BC) cells by mediating the Wnt/β-catenin signaling pathway. BC and adjacent normal tissues were collected from 165 BC patients. Western blotting and quantitative real-time PCR were used to detect the expression of GSK3β, β-catenin, cyclinD1, E-cadherin, vimentin and miR-135a in BC tissues and cells. Cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…The invasion ability shown by means of the transwell analysis declined dramatically too. 22,23 Taking all the above results together, we demonstrated here that NSCs/NPCs had inhibitory effects on the growth and invasion of U87 glioma in vitro might do so via affecting the growth and invasion of U87 stemlike cells. And possibly, this effect was executed through the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 56%
“…The invasion ability shown by means of the transwell analysis declined dramatically too. 22,23 Taking all the above results together, we demonstrated here that NSCs/NPCs had inhibitory effects on the growth and invasion of U87 glioma in vitro might do so via affecting the growth and invasion of U87 stemlike cells. And possibly, this effect was executed through the PI3K/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 56%
“…In colon adenocarcinoma, miR‐135a was suggested to be a "sponge" of lncRNA FOXD3‐AS1 to regulate cell proliferation, migration, invasion, and apoptosis by targeting SIRT1 . In addition, several studies have also revealed that the positive effects of miR‐135a on BC cell proliferation, epithelial‐mesenchymal transition, migration and invasion . However, whether miR‐135a participated in the regulation of MBNL1‐AS1 in BC progression remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that the expression levels of Wnt factors are significantly upregulated in bladder cancer (30,31), and the Wnt/β-catenin signalling is important in the malignant progression of bladder cancer (32,33). For example, Shen et al showed that the levels of β-catenin in human bladder cancer tissues were upregulated with increasing grade of malignancy (30).…”
Section: Discussionmentioning
confidence: 99%